Towards better Schools and more Equal Opportunities for Learning in Italy - Boarini, Romina (OECD Publishing, 2009)
Compulsory school education in Italy produces poor results in terms of 15-year olds' performance on PISA tests, compared with other OECD countries, despite a relatively high level of expenditure. While the influence of social background is smaller than in many OECD countries, it is largely transmitted through a kind of self-segregation resulting from family choices among the different types of upper secondary school. Large differences in pupils' performance between regions cannot be explained by the quantity of resources available; separating the influence of socio-economic conditions from school efficiency is difficult and must be treated carefully in plans for extending fiscal federalism. The Italian government is rightly concerned to get better value for money and this chapter argues that policies to improve the information available to schools and teachers on the results they are achieving, while giving them appropriate incentives, responsibility and power to respond to such information, are necessary accompaniments to expenditure-saving policies. An improved focus on good quality training, both for new recruits and experienced teachers, and recruitment procedures themselves, should also pay dividends on efficiency
Keywords: Economics; Italy